2018
DOI: 10.1007/s00122-018-3107-5
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping of pre-harvest sprouting resistance in a white wheat cultivar Danby

Abstract: One major and three minor QTLs for resistance to pre-harvest sprouting (PHS) were identified from a white wheat variety "Danby." The major QTL on chromosome 3A is TaPHS1, and the sequence variation in its promoter region was responsible for the PHS resistance. Additive × additive effects were detected between two minor QTLs on chromosomes 3B and 5A, which can greatly enhance the PHS resistance. Pre-harvest sprouting (PHS) causes significant losses in yield and quality in wheat. White wheat is usually more susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 83 publications
2
29
0
1
Order By: Relevance
“…However, in this study, the selected backcrossing progenies with both resistance genes still showed higher average germination rates than their PHS-resistant donors in most experiments (Tables 1 and 3), suggesting that other minor genes in both donor parents might also be important for reducing PHS [33]. Identifying and accumulating natural mutations and the non-grain color related resistance QTLs with TaPHS1 and TaMKK3-A could greatly enhance the PHS resistance in white wheat [3,19].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…However, in this study, the selected backcrossing progenies with both resistance genes still showed higher average germination rates than their PHS-resistant donors in most experiments (Tables 1 and 3), suggesting that other minor genes in both donor parents might also be important for reducing PHS [33]. Identifying and accumulating natural mutations and the non-grain color related resistance QTLs with TaPHS1 and TaMKK3-A could greatly enhance the PHS resistance in white wheat [3,19].…”
Section: Discussionmentioning
confidence: 64%
“…To avoid confusion between TaPHS1 and Phs1, we use TaPHS1 for the gene on 3AS and TaMKK3-A for the gene on 4AS hereafter. Although several other QTLs have been reported to be associated with PHS resistance [17][18][19], only TaPHS1 and TaMKK3-A have been cloned and validated to show major effects in multiple backgrounds [4][5][6]15].…”
Section: Introductionmentioning
confidence: 99%
“…The Amplifluor-like marker assay contained 40 ng template DNA (or 2 μl 1:10 diluted cDNA), 0.4 μM each of universal probes, 0.3 μM each of forward primers, 0.6 μM reverse primer, 0.2 mM dNTPs, 1 × Taq buffer (+Mg 2+ ) and 0.75 denaturation 5 s and 61 °C annealing 20 s in each cycle. The KASP marker was carried out following a standard KASP procedure (www.lgcgr oup.com) which was widely applied in bread wheat (Rasheed et al 2016;Shao et al 2018). The KASP reaction included 1 × KASP Master Mix, 0.4 mM MgCl 2 , 40 ng DNA template, 0.14 μM each of the allelespecific forward primers and 0.36 μM reverse primer in a final volume of 5 μl reaction.…”
Section: Development Of Allele-specific Marker and Genotypingmentioning
confidence: 99%
“…Seed dormancy is a highly complex trait and largely influenced by genetic and environmental factors [4]. Recent progress in plant genomics and various genetic populations has facilitated the identification of quantitative trait loci (QTLs) for seed dormancy in many species, for example, in Arabidopsis [5], Lepidium sativum [6], oilseed rape [7], sorghum [8], barley [9], and wheat [10][11][12].…”
Section: Introductionmentioning
confidence: 99%